The Role Of Digital Marketing In Traditional Market Competitiveness Of Sokobanah Daya MSMES - Muh Rizal Muhaimin Romadhoni; Desy Bariyyatul Qibtiyah (International Journal of Management and Business Economics, 2026)
The development of digital technology has changed marketing patterns and consumer behavior; however, not all business sectors, including traditional markets, are able to adapt to these changes. This study analyzes the implementation of digital marketing among MSMEs in the Sokobanah Daya Traditional Market and its impact on consumer behavior and traditional market competitiveness. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation involving 5 MSME operators and 2 consumers. Data analysis was conducted using the Miles and Huberman model. The findings show that the implementation of digital marketing remains low, as most MSME operators still rely on conventional marketing methods. Low digital literacy and limited technical skills are the main inhibiting factors. The development of digital marketing has shifted consumer behavior toward online shopping, thereby reducing the competitiveness of traditional markets. Nevertheless, traditional markets still maintain the advantage of direct interaction. This study contributes to understanding the challenges of digital transformation among traditional market MSMEs in rural areas. Therefore, improving digital literacy and integrating conventional and digital marketing strategies are necessary to support the sustainability of traditional markets.